Differentiating Text-Based and Knowledge-Based Validation Processes during Reading: Evidence from Eye Movements. Issue 1 (2nd January 2021) - van Moort, Marianne L.; Koornneef, Arnout; van den Broek, Paul W.
ABSTRACT: To build a coherent accurate mental representation of a text, readers routinely validate information they read against the preceding text and their background knowledge. It is clear that both sources affect processing, but when and how they exert their influence remains unclear. To examine the time course and cognitive architecture of text-based and knowledge-based validation processes, we used eye-tracking methodology. Participants read versions of texts that varied systematically in (in)coherence with prior text or background knowledge. Contradictions with respect to prior text and background knowledge both were found to disrupt reading but in different ways: The two types of contradiction led to distinct patterns of processes, and, importantly, these differences were evident already in early processing stages. Moreover, knowledge-based incoherence triggered more pervasive and longer (repair) processes than did text-based incoherence. Finally, processing of text-based and knowledge-based incoherence was not influenced by readers' working memory capacity.